MODEL P BACK ORDER DAN ALGORITMA PERMASALAHAN INVENTORI DENGAN MEMPERTIMBANGKAN ONGKOS TRANSPORTASI (FIXED AND VARIABLE COST) – PERMINTAAN PROBABILISTIK - Burhan Burhan (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
P Model of inventory for solving problem of controlling inventory is taking into account a probabilistic consumer’s demand. Transportation cost is included in calculating of total inventory cost. The solution of this model is done by Hadley – Within method. Thedecision variables of this research are: time period of ordering, the maximum inventory in hand, and the safety stock. A numerical example is provided to illustrate model mechanism in determining these decision variables. According to the numerical example, it can be concluded that there is saving of inventory total cost, by comparing the result to the existing model.